Identification of an ancient Bmp4 mesoderm enhancer located 46 kilobases from the promoter - Chandler, Kelly J. (2009)
Bone morphogenetic protein 4 (Bmp4) is a multi-functional, developmentally regulated gene that is essential for mouse development, as most Bmp4-null mouse embyros die at the onset of gastrulation and fail to develop mesoderm. Little is known about the transcriptional regulation of Bmp4. To identify potential long-range cis-regulatory elements that direct its complex spatiotemporal expression patterns, we surveyed the mouse Bmp4 locus using two overlapping bacterial artificial chromosome (BAC) reporter transgenes. Our findings indicate that tissue-specific cis-regulatory elements reside greater than 28 kilobases 5’ or 3’ to the mouse Bmp4 transcription unit. In addition, comparative analyses identified three noncoding evolutionarily conserved regions (ECRs), spaced around the gene and conserved from mammals to fish, that are maintained in a syntenic group across vertebrates. Deletion of one of these conserved sequences (ECR2) from a BAC transgene revealed a tissue-specific requirement for ECR2 in driving Bmp4 expression in extraembryonic and embryonic mesoderm. Furthermore, a 467 bp mouse sequence containing ECR2 reproducibly directed lacZ minigene expression in mesoderm. Taken together, this shows an ancient, mesoderm-specific cis-regulatory element resides nearly 50 kilobases 5’ to mouse Bmp4.